Enhanced Microwave Absorption Properties of FeCo@TiO2 Core-Shell Nanoparticles - Gharaati, Abdolrasoul; Ebrahimzadeh, Majid (Current Nanoscience, 2019)
Background: Microwave absorbing nanocomposite is a kind of material that attenuates the reflection of microwave radiation in the gigahertz frequency range. These materials consist of dielectric and transition nanoparticles tend to exhibit attractive microwave absorption properties due to their high permittivity and permeability loss factors. Method: The FeCo nanoparticles were prepared from the reduction of iron and cobalt ions with hydrazine. Then, the FeCo@TiO2 core-shell nanoparticles synthesized by co-precipitation method and their microwave absorbing performance are investigated. The phase composition, morphology and coercivity properties of the nanoparticles were studied by X-ray diffraction (XRD), transmission electron microscopy (TEM) and vibrating sample magnetometry (VSM). The composites of FeCo@TiO2 nanoparticles with the ratio of 30 vol.% and paraffin wax (70 vol.%) in different thicknesses were prepared. The microwave absorption properties of these composites were investigated in the frequency range of 2-18 GHz using the vector network analyzer. Results: These nanocomposites exhibit the excellent microwave absorption characteristics (reflection loss<-20dB) in the bored band frequency range of 6-16 GHz with different absorber thicknesses of 1- 2.2 mm. The maximum absorption capability of -47.76 dB was obtained at the frequency of 7.92 GHz with the thickness of 1.8 mm. Conclusion: Based on this study, it can be argued that the FeCo@TiO2 nanoparticles can be used for the bored band and thin microwave absorbers.
Keywords: permeability